PRAKTIK PINJAM MEMINJAM PADA KOPERASI DESA KOTA INDONESIA DI INDRAMAYU DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Abidin, Zaenal; Prawoto, Imam; Sulistyani, Anjar (Journal of Islamic Studies, 2023)
The practice of savings and loans is considered as an choices when someone cannot fulfill their basic needs yet in cash. The main purpose of savings and loans practice is to help each other, until when someone gives loans to other people with the purpose to help each other then it will be valued as devotion (worship). From the background above, then the researcher proposed a research question namely about the practice of savings and loans at Cooperative Institution of Village City Indonesia in Indramayu Regency in the perspective of positive law and Islamic law. Researchers utilize a qualitative approach; this research is conducted in the field (field research), where the best conditions for doing research are present. Researchers gather data using a variety of techniques, including population and sample surveys, recordkeeping, and interview techniques. Purposive sampling is a non-random sampling technique that researchers use to determine their sample size. It is a sample determination technique with specific considerations, and it allows researchers to draw conclusions by identifying specific characteristics that are in line with their research objectives. According to the findings of the study, lending was done in a way that complied with positive law at KSU Village City Indonesia, where savings and loans were practiced.This was based on The Law Number 10 Year 1998 about the deal and agreement of savings and loans. And this was also suitable with Islamic law namely the presence of someone’s willingness to help each other by using tauhid, halal, and ibahah principles.